Utrata wartości aktywów-zabezpieczeń w aspekcie tworzenia rezerw celowych w bankach komercyjnych - Biernacki, Michał (Secure-Assets Value Loss in the Aspect of Creation the Appropriated Reserves in Commercial Banks, 2005)
In the following article there were described basic area of assets value loss determining secure in the commercial banks, in the aspect of creating the appropriated reserves of credit exposition, and also their exposition in financial statements. The attention should be paid to the fact that creating the appropriated reserves is mandatory for each commercial bank and there should not appear situation, in which the activation of reserve value in purpose of indicating high financial result will take place. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 104-109